Beyond the composite abuse scale: what women emphasize about their intimate partner's violence - Tutty, Leslie M. (Journal of interpersonal violence, 2025)
The Healing Journey longitudinal study of 665 Canadian women abused by intimate partners used the 30-item Composite Abuse Scale (CAS) to assess the severity of the intimate partner violence (IPV). Of the total, 461 women added additional details that were qualitatively analyzed to provide context to the IPV, including death threats, life-threatening physical violence, including strangulation, and serious coercive control, issues not assessed by the CAS. Further, many partners were abusive beyond the couple relationship, threatening family members, children, and pets, and also not in the CAS. We then retrospectively reviewed other IPV measures to consider whether these might have more comprehensively fit with the women’s experiences. Of these, four IPV measures more fully captured the women’s descriptions of their IPV than the CAS (three available before and one after the study was conceptualized). This retrospective analysis provides suggestions for using standardized measures to assess IPV more comprehensively.